Cyprosulfamide effectively alleviates flusulfinam phytotoxicity in maize with enhanced dissipation - Yu Wang; Junqi Zhu; Mingdong Deng; Huijin Lin; Huanyu Zhou; Wenyu Dai; Ya Zhou; Tengfei Zhang; Yanmei Liu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Simultaneous desulfurization and magnetization in suspension roasting of high-sulfur and high-iron bauxite for aluminum–iron separation - Ruoxin Li; Chaoyi Chen; Junqi Li; Guoliang Wei; Xin Lin; Gangan Wang (Minerals Engineering, 2026)

Tailored high internal phase emulsion-filled/emulsion particulate gels based on gelatin/agar by cold gelation: stability, rheological behaviors, and delivery properties - Fengrui Zhang; Zhishuang Ma; Junqi Han; Xingbin Yang; Dehui Lin (Food Hydrocolloids, 2026)

Alkali-circulation-mediated valorization of fluorine-rich silica residue and carbide slag: Coproduction of hydrated silica and calcium fluoride - Gangan Wang; Chaoyi Chen; Junqi Li; Tianxin Li; Xin Lin; Guoliang Wei (Journal of Hazardous Materials, 2026)

The effect of Co-fermentation with Saccharomyces cerevisiae and Latilactobacillus sakei on the quality of rose-flavored kvass - Maierhaba Maimaitiabula; Junqi Chao; Mingshou Lü; Lin Xi; Lei Gao; Yufu Zhao; Hongchen Fan; Kai Zhao (Food Bioscience, 2026)

Reconstructing the Seawater Temperature Field of the Yellow Sea Using TCN-U-Net++ - Jiapeng Bu; Zi Guo; Junqi Cui; Shuyi Zhou; Lei Lin; Shaolei Lu; Xiaodong Liu; Xiaoqian Gao (Journal of Marine Science and Engineering, 2026)
The Yellow Sea is an important offshore area in China, and the accurate prediction of its seawater temperature is of great significance for marine environmental monitoring and climate adaptation management. However, existing research on predicting the three-dimensional (3D) temperature field in the Yellow Sea is scarce and insufficiently accurate. This study proposes a TCN-U-Net++ fusion model to reconstruct the Yellow Sea temperature field using remote sensing satellite data and SODA reanalysis data, while considering the influence of a series of factors, including wind (USSW and VSSW), absolute bathymetric data (BAT), sea surface height anomaly (SSHA), latitude (LAT), longitude (LON), solar radiation (SR), surface runoff (SRO), and precipitation (P). The results show that the model can accurately capture the temporal and spatial distribution characteristics of the temperature field in the Yellow Sea. The results indicate that the deviations from SODA are generally within 2 °C, with errors being approximately 45% lower than those of other models, while the prediction errors relative to Argo and voyage observations are mostly within 1 °C, further demonstrating the accuracy and robustness of the proposed model. In addition, the predictions of the Yellow Sea Cold Water Mass (CWM) are highly consistent with SODA in terms of their evolution and key characteristic parameters. Specifically, the maximum deviation in core temperature is only 0.3 °C, and the difference in its spatial extent is less than 1%. The results demonstrate that TCN-U-Net++ effectively enhances the accuracy of 3D sea temperature prediction in the Yellow Sea, providing technical support for temperature monitoring, ecological early warning, and climate change research.

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Fine mapping and preliminary mechanism analysis of tobacco Fusarium root rot resistance genes - Yang Shen; Junqi Cheng; Chao Fu; Chenglin Wu; Yapei Li; Zhongxu Lin; Jinglin Cao (Physiological and Molecular Plant Pathology, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Ozone Exposure Risks in Urban Outdoor Activities: Built Environment Determinants and Policy Implications for Sustainable Cities - Li Han; Yongjie Qi; Junqi Wang; Lin Luo; Shi-Jie Cao (Building and Environment, 2026)

Chronic exposure to low concentration of metamifop induces reproductive endocrine disruption and courtship behavior disorders in zebrafish (Danio rerio) - Lu Lin; Feng Zhao; Jingjing Wu; Yihao Zhao; Junqi Zhu; Tengfei Zhang; Huihua Tang; Tao Tang; Lihong Qiu (Environmental Research, 2025)

U-RNN high-resolution spatiotemporal nowcasting of urban flooding - Xiaoyan Cao; Baoying Wang; Yao Yao; Lin Zhang; Yanwen Xing; Junqi Mao; Runqiao Zhang; Guangtao Fu; Alistair G.L. Borthwick; Huapeng Qin (Journal of Hydrology, 2025)

Genetic diversity and population structure of 305 tobacco accessions revealed by simple sequence repeats (SSRs) and newly developed insertion-deletion (Indels) polymorphisms - Yang Shen; Chenglin Wu; Junqi Cheng; Yapei Li; Zhongxu Lin; Jinglin Cao (Genetic Resources and Crop Evolution, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Seismic fragility analysis of three-tower cable-stayed bridges with different connection configurations - Chen Chen; Jinlong Liu; Junqi Lin; Suchao Li (Earthquake Engineering and Engineering Vibration, 2024)

High-performance elimination of Cr(VI) in actual wastewater with a novel nZVI-based composite anchoring onto amino-grafted chitosan - Lixin Huang; Junqi Wei; Haiying Lin; Bin Xue; Yu Duan; Mingzhi Li; Zixuan Chen; Jiatong Lv; Lianghong Li; Xianghua Wu; Qiuyan Hu (Journal of Water Process Engineering, 2024)

Complete long-term monitoring of greenhouse gas emissions from a full-scale industrial wastewater treatment plant with different cover configurations - Qinyi Wang; Yangyue Sheng; Yili Zhang; Xinrun Zhong; Hui Liu; Zhengfeng Huang; Dan Li; Hao Wu; Yuanzhi Ni; Junqi Zhang; Weiqing Lin; Kaipei Qiu; et al. (Journal of Environmental Management, 2024)

A coarse-to-fine visual geo-localization method for GNSS-denied UAV with oblique-view imagery - Qin Ye; Junqi Luo; Yi Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Ultra-low electrical loss superconducting cables for railway transportation: Technical, economic, and environmental analysis - Yu Chen; Lin Fu; Xiaoyuan Chen; Shan Jiang; Xiaohong Chen; Junqi Xu; Boyang Shen (Journal of Cleaner Production, 2024)

Developmental toxicity and metabolomics analyses of zebrafish (Danio rerio) embryos exposed to Fenoxaprop-p-ethyl - Feng Zhao; Lu Lin; Yihao Zhao; Jingjing Wu; Junqi Zhu; Tengfei Zhang; Huihua Tan (Environmental Science and Pollution Research, 2024)

The adsorption and release mechanism of different aged microplastics toward Hg(II) via batch experiment and the deep learning method - Lianghong Li; Bin Xue; Haiying Lin; Wenlu Lan; Xinyi Wang; Junqi Wei; Mingen Li; Mingzhi Li; Yu Duan; Jiatong Lv; Zixuan Chen (Chemosphere, 2024)

A clean method for gallium recovery and the coproduction of silica-potassium compound fertilizer and zeolite F from brown corundum fly ash - Gangan Wang; Chaoyi Chen; Junqi Li; Fan Yang; Linzhu Wang; Xin Lin; Hao Wu; Jun Zhang (Journal of Hazardous Materials, 2024)

Boosting the charge transport and stability of metal halide perovskite with boron nitride nanosheets for X-ray detection and imaging - Fang Yao; Zhenglin Jia; Junqi Dong; Ruiming Li; Yujie Yang; Haitao Tang; Wusheng Zou; Jiangbin Zhao; Yong Liu; Zhu Wang; Gaokui He; Qianqian Lin (Chemical Engineering Journal, 2024)

Effect of low-temperature stress on transcriptome and Na+/K+-ATPase changes in Oreochromis niloticus gill tissues - Zhe Li; Luting Wen; Junqi Qin; Zhong Chen; Xianhui Pan; Kangqi Zhou; Yin Huang; Qian Deng; Yong Lin; Xuesong Du (Ichthyological Research, 2023)

One-step synthesis of thiol-functionalized metal coordination polymers: effective and superfast removal of Hg (II) in the different matrices to ppb level - Mingzhi Li; Yongjie Tuo; Qiuxia Wu; Haiying Lin; Qingge Feng; Yu Duan; Junqi Wei; Zixuan Chen; Jiatong Lv; Lianghong Li (Chemosphere, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

30 Years of Climate Change before and after the Impoundment of the Three Gorges Reservoir - Junqi Liu; Chen Lin; Shan Dong; Ruixue Feng; Aijun Su; Jinghui Cui; Shupeng Yu (Journal of Earth Science, 2023)

A temporally relaxed theory of physically or chemically non-equilibrium solute transport in heterogeneous porous media - Ying-Fan Lin; Junqi Huang; Elliot J. Carr; Tung-Chou Hsieh; Hongbin Zhan; Hwa-Lung Yu (Journal of Hydrology, 2023)

High temporal resolution urban flood prediction using attention-based LSTM models - Lin Zhang; Huapeng Qin; Junqi Mao; Xiaoyan Cao; Guangtao Fu (Journal of Hydrology, 2023)

Genome-wide association study reveals markers and candidate genes associated with growth in the rice flower carp, an economic fish species of integrated rice-fish culture in China - Hui Luo; Xianhui Pan; Yin Huang; Zhe Li; Hua Ye; Kangqi Zhou; Luting Wen; Junqi Qin; Wenping He; Xuesong Du; Dapeng Wang; Yong Lin (Frontiers in Marine Science, 2023)
The rice flower carp ( Cyprinus carpio ) is an important fish in integrated rice-fishery farming. Here, we performed the first genome-wide association study (GWAS) for seven growth traits (including body mass, total length, body length, body height, body width, caudal-peduncle depth, and eye spacing) in 200 rice flower carp samples using 369,688 high-quality SNPs and 42,225 indels obtained by double-digest genotyping-by-sequencing (ddGBS). The morphometrics of these traits were highly correlated (Pearson’s correlation coefficients = 0.74–0.99, p < 0.001). GWAS detected 15, 5, 4, 26, 7, 16, and 17 loci significant associated (-log10P ≥ 5) with body mass, total length, body length, body width, body height, caudal-peduncle depth, and eye spacing, respectively. Subsequently, within the 50 kb upstream and downstream regions surrounding these significant loci, 38, 19, 18, 20, 52, 27, and 37 candidate genes for the seven growth traits were detected, respectively. Importantly, B6_4352672 and A8_4978825 were significantly associated with more than five growth traits. These results showed loci significantly associated with more than five growth traits will be helpful for future marker-assisted selection (MAS). Interestingly, chromosomes A8 and B25 had many loci significantly associated with growth traits, most of which were shared among multiple growth-related traits. These results indicated that chromosome A8 and B25 may be closely related to growth traits. Our findings not only help understand the genetic architecture of growth traits in fish but facilitate the identification of candidate genes for marker-assisted selection towards breeding faster-growing rice flower carp in the future.

Time-varying seismic fragility analysis of bridges under the condition of the scour and freeze–thaw cycles - Tinghui Li; Junqi Lin; Jinlong Liu (European Journal of Environmental and Civil Engineering, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Grouting Effect on Reinforcement of Weathered Granite - Jian Zhang; Shucai Li; Zhaofeng Li; Qingsong Zhang; Lei Yang; Junqi Du; Hengtian Li; Yanhai Qi; Rongfeng Lin (Geotechnical and Geological Engineering, 2020)

Correction to: Development and validation of EST-SSR markers of Magnolia wufengensis using de novo transcriptome sequencing - Li Wang; Xiaoqiang Gong; Lin Jin; Haiying Li; Junqi Lu; Jie Duan; Luyi Ma (Trees, 2019)

Development and validation of EST-SSR markers of Magnolia wufengensis using de novo transcriptome sequencing - Li Wang; Xiaoqiang Gong; Lin Jin; Haiying Li; Junqi Lu; Jie Duan; Luyi Ma (Trees, 2019)

Field investigation on severely damaged aseismic buildings in 2014 Ludian earthquake - Xuchuan Lin; Haoyu Zhang; Hongfu Chen; Hao Chen; Junqi Lin (Earthquake Engineering and Engineering Vibration, 2015)

Coordinated regulation of autophagy and apoptosis determines endothelial cell fate during Dengue virus type 2 infection - Junqi Huang; Ying Li; Yiming Qi; Yingke Zhang; Lin Zhang; Zilian Wang; Xuzhi Zhang; Lian Gui (Molecular and Cellular Biochemistry, 2014)